Gabrielle Andreozzi: capstone - Andreozzi, Gabrielle, artist (Colorado State University. Libraries, 2021)
The artist's statement: Motions of the unsaid: a series of the self. Spending a year in pandemic has been cause for much self-reflection and reinvention of the self. Forced solitude, manifested both physically and mentally, caused me to realize how uncomfortable with introspection and out of touch with myself I had become. Over the course of a single year, I have gone through more change within my reality than I have in my entire life. I have always been inspired by the way photographic imagery can capture a moment in time that is much too fleeting to be perceived by the naked eye. With one burst of a shutter, these snapshots can be frozen in time, existing past the moment and into the future - forgetting the specificity but remembering and honoring what was and has been. The self-portraiture within this series captures my subconscious experience of growth and emergence through everything I have gone through as a young woman - a visual exploratory event of the transformation unfolding within me that I have not had the words to express. The ambiguous and ever flowing nature of my being is something that I have come to embrace - every beautiful moment I wish I could live in forever, every painful moment when my heart has hurt more than I could have ever imagined - no longer trying to battle against their remembrance out of fear of exposing myself and my vulnerability. These are the motions of my metamorphosis.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: photo image making